A cDNA Clone-Launched Platform for High-Yield Production of Inactivated Zika Vaccine - Yujiao Yang; Chao Shan; Jing Zou; Antonio E. Muruato; Diniz Nunes Bruno; Barbosa de Almeida Medeiros Daniele; Pedro F.C. Vasconcelos; Shannan L. Rossi; Scott C. Weaver; Xuping Xie; Pei-Yong Shi (EBioMedicine, 2017)
A purified inactivated vaccine (PIV) using the Zika virus (ZIKV) Puerto Rico strain PRVABC59 showed efficacy in monkeys, and is currently in a phase I clinical trial. High-yield manufacture of this PIV is essential for its development and vaccine access. Here we report an infectious cDNA clone-launched platform to maximize its yield. A single NS1 protein substitution (K265E) was identified to increase ZIKV replication on Vero cells (a cell line approved for vaccine production) for both Cambodian FSS13025 and Puerto Rico PRVABC59 strains. The NS1 mutation did not affect viral RNA synthesis, but significantly increased virion assembly through an increased interaction between NS1 and NS2A (a known regulator of flavivirus assembly). The NS1 mutant virus retained wild-type virulence in the A129 mouse model, but decreased its competence to infect Aedes aegypti mosquitoes. To further increase virus yield, we constructed an infectious cDNA clone of the clinical trial PIV strain PRVABC59 containing three viral replication-enhancing mutations (NS1 K265E, prM H83R, and NS3 S356F). The mutant cDNA clone produced >25-fold more ZIKV than the wild-type parent on Vero cells. This cDNA clone-launched manufacture platform has the advantages of higher virus yield, shortened manufacture time, and minimized chance of contamination.